التربية بالمواقف و المناسبات وأثرها في تأهيل الناشئة - SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUN, ISKANDI IAIN (Tarbawy : Jurnal Pendidikan Islam, 2024)
The article begins with the importance of educational action and its necessity for the continuity and the quality of human life in the present and future. It highlights the types of educational actions, their various methods, and their reflection on the personality and behavior of educators. The article addresses the problems of neglect, misuse, and educational misemployment in situations and events, and their effect on the future of youth and civilization of nations. Education through situations and events has been a traditional and contemporary method of education, proven to have a strong impact on youth in the long, medium, and sometimes immediate term. The study distinguishes between levels of situations and events based on their cognitive, historical, and cultural content, and the achievements they strive to realize in terms of of ethics and values. It categorizes them as ordinary situations experienced by the public, infrequent occurrences, specific national events, or religious events characterized by general acceptance and consensus. The study emphasizes measuring the importance of situations and events and their impact on youth, planning ways to introduce and utilize them in education beyond coercive methods, fostering genuine human influence. In this context, the study proposes educational approaches and methods to activate the roles of this educational style.